Efficacy and Safety of Chemotherapy Regimens in Advanced or Metastatic Bladder and Urothelial Carcinomas: An Updated Network Meta-Analysis - Qu, Hong-Chen; Huang, Yan; Mu, Zhong-Yi; Lv, Hang; Xie, Qing-Peng; Wang, Kai; Hu, Bin (Frontiers in Pharmacology, 2020)
Background Gemcitabine plus cisplatin (GC) and methotrexate, vinblastine, adriamycin, and cisplatin (MVAC) have been the first-line treatments for advanced or metastatic urothelial carcinoma (AMUC). However, their effects are unsatisfactory, and more drugs and regimens still need to be explored. Objective We aimed to comprehensively compare all possible regimens with GC or MVAC in randomized controlled trials (RCTs) by network meta-analysis. Methods We searched the PubMed, Embase, and Cochrane databases for RCTs that evaluated regimens compared to GC or MVAC on AMUC patients. The major outcomes were progression-free survival (PFS), overall survival (OS), and objective response rate (ORR). A network meta-analysis was used to assess the effectiveness and safety of the included treatment regimens, and the regimens were then clustered by the average linkage method. Results A total of 19 trials that assessed 3363 AMUC patients were included. For PFS, paclitaxel plus GC (PGC) was significantly superior to GC (log hazard ratio (HR): -0.16; 95% confidence interval (CI): -0.32, 0.00) with a moderate level of reliability. However, there was no significant difference between PGC and MVAC (log HR: -0.03; 95% CI: -0.27, 0.20). For OS, PGC was significantly superior to GC (log HR:-0.17; 95% CI: -0.33, -0.00) with a moderate reliability level but not significantly different from MVAC (log HR: -0.10; 95% CI: -0.35, 0.15). Analysis of ORR showed that PGC was superior to MVAC (log odds ratio (OR): 0.59; 95% CI: 0.02, 1.16) with a low reliability level and GC (log OR: 0.41; 95% CI: 0.12, 0.71) with a moderate reliability level. In the cluster results, PGC and sorafenib plus GC (GCS) exhibited relative advantages in efficiency, followed by MVAC and apatorsen plus GC (GCA); however, PGC, gemcitabine plus carboplatin (GP) and MVAC had more serious side effects. Conclusions In our analysis, PGC was superior to MVAC and GC in only the ORR results and superior to GC in the OS and PFS results but was not significantly different from MVAC. More individualized therapies with targeted drugs need to be studied.